THE INFLUENCE FACTORS EMPLOYEE JOB SATISFACTION ON EMPLOYEE PERFORMANCE IN THE PPKUKM ADMINISTRATIVE CITY OF EAST JAKARTA - Safitri, Ayu; Krisnandi, Herry (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2025)
This study analyzed the effect of compensation, work environment, and human resources quality through job satisfaction on employee performance. The research sample was 124 people with simple random sampling. The research approach is a quantitative method. Data collection techniques were carried out by interviews and closed questionnaires with an interval scale of 1 to 5 gradation. The data analysis technique used SmartPLS Ver4.0. The findings of the study showed that compensation and work environment did not have a positive and significant effect on job satisfaction. While the human resources quality had a positive and significant effect on job satisfaction. Compensation and environment also did not have a positive and significant effect on employee performance while the human resources quality had a positive and significant effect on employee performance. Compensation and work environment did not have a positive and significant effect on employee performance through employee job satisfaction while the human resources quality had a positive and significant effect on employee performance through employee job satisfaction.